Physical, Chemical and Antioxidant Properties of Tarhana with Cornelian Cherry - Faik Koca, Ahmet (Asian Journal of Chemistry, 2010)
In this study, physical, chemical and antioxidant properties of tarhana with cornelian cherry were determined. The lowest and highest values of investigated parameters were as follows: Hunter L from 41.14 to 62.12, a from +5.93 to +24.67, b +7.99 to +14.05, water activity from 0.292 to 0.695, moisture content from 6.20 to 15.74, pH from 3.42 to 3.96, titratable acidity from 0.17 to 1.26 %, protein from 11.08 to 22.33 % (on dry basis), ash from 1.59 to 4.10 % (on dry basis), salt from 0.27 to 2.89 % (on dry basis), total anthocyanin value from 12.03 to 41.81 mg kg-1, total phenolics from 357.40 to 762.81 mg kg-1, total antioxidant activity from 2.79 to 12.47 mM.